Determinants of poor sleep quality in adults during the coronavirus disease pandemic: COVID-Inconfidentes, a population-based study - Meireles, Adriana Lúcia; Júnior, Luiz Antônio Alves de Menezes; Lourenção, Luciano Garcia; Andrade, Amanda Cristina de Souza; Carraro, Júlia Cristina Cardoso; Coelho, George Luiz Lins Machado (São Paulo Medical Journal, 2023)
BACKGROUND: The coronavirus disease (COVID-19) pandemic has adversely affected the health of the global population, with sleep quality being one of the affected parameters. OBJECTIVES: To evaluate sleep quality and its associated factors in adults during the COVID-19 pandemic in Brazil. DESIGN AND SETTING: A population-based cross-sectional serological survey of 1,762 adults in the Iron Quadrangle region of Brazil. METHODS: The Pittsburgh Sleep Quality Index was used to assess sleep quality. Sociodemographic variables, health conditions, health-related behaviors, anxiety, vitamin D levels, weight gain/loss, and pandemic characteristics were assessed using a structured questionnaire. Univariate and multivariate analyses using Poisson regression with robust variance were performed to identify factors associated with sleep quality. RESULTS: More than half of the participants reported poor sleep quality (52.5%). Multivariate analysis revealed that the factors associated with poor sleep quality included living alone (prevalence ratio [PR] = 1.34; 95% confidence interval [CI]: 1.04–1.73), anxiety disorder (PR = 1.32; 95% CI: 1.08–1.62), 5.0% weight loss (PR = 1.21; 95% CI: 1.02–1.44), 5.0% weight gain (PR = 1.27; 95% CI: 1.03–1.55), vitamin D deficiency (PR = 1.16; 95% CI: 1.01–1.35), and COVID-19 symptoms (PR = 1.29; 95% CI: 1.10–1.52). CONCLUSIONS: Our study revealed that more than half of the participants experienced poor sleep quality during the COVID-19 pandemic. Factors associated with poor sleep quality included vitamin D deficiency and weight changes related to the pandemic.